2003
DOI: 10.1128/aem.69.8.5019-5022.2003
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Mating-Type Loci of Cordyceps takaomontana

Abstract: Nucleotide sequences of the mating-type loci MAT1-1 and MAT1-2 of Cordyceps takaomontana were determined, which is the first such report for the clavicipitaceous fungi. MAT1-1 contains two mating-type genes, MAT1-1-1 and MAT1-1-2, but MAT1-1-3 could not be found. On the other hand, MAT1-2 has MAT1-2-1. A pseudogene of MAT1-1-1 is located next to MAT1-2.Entomopathogenic fungus Paecilomyces tenuipes is an anamorph of Cordyceps takaomontana (Ascomycota: Pyrenomycetes: Hypocreales [Clavicipitales]: Clavicipitaceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 23 publications
3
37
0
Order By: Relevance
“…These results are also consistent with other studies in fungi: in almost all the putatively asexual species where mating type genes have been sequenced, they presented no evidence of loss-of-function mutations (O'Donnell et al, 2004). Only in the entomopathogenic fungus Cordyceps takaomontana did mating type loci contain pseudogenes (Yokoyama et al, 2003). This suggests that in most fungi, mating type genes may still be functional, which is not expected if these species were truly asexual for long.…”
Section: Discussionsupporting
confidence: 91%
“…These results are also consistent with other studies in fungi: in almost all the putatively asexual species where mating type genes have been sequenced, they presented no evidence of loss-of-function mutations (O'Donnell et al, 2004). Only in the entomopathogenic fungus Cordyceps takaomontana did mating type loci contain pseudogenes (Yokoyama et al, 2003). This suggests that in most fungi, mating type genes may still be functional, which is not expected if these species were truly asexual for long.…”
Section: Discussionsupporting
confidence: 91%
“…We were also able to identify (Coppin et al 1997;Turgeon and Yoder 2000). However, similar structures have also been observed in the MAT1-2 idiomorphs of few other heterothallic Sordariomycetes, where pseudogenes, partial sequences, or homologs of MAT1-1 genes are present in the MAT1-2 idiomorph (Kanematsu et al 2007;Wilken et al 2012;Yokoyama et al 2003).…”
Section: Discussionsupporting
confidence: 77%
“…Evidence for MAT1-1-1 transcripts has been acquired by RT-PCR, but the transcriptional state of MAT1-1-2 is unknown. The MAT1-2 idiomorph contains the expected MAT1-2-1 gene but Yokoyama et al (2003) have identified an additional putative MAT1-1-1 pseudogene in this idiomorph. This pseudogene lacks the region encoding the α1 box, and the ORF has no initiation codon and is interrupted by several termination codons.…”
Section: C) Asexual Sordariomycetesmentioning
confidence: 97%
“…Transcripts for each of the MAT genes of F. oxysporum were found by RT-PCR, suggesting that the asexual feature of F. oxysporum does not result from a transcriptional deficiency. A total of 22 isolates of another asexual hypocreales, P. tenuipes (the sexual state of Cordyceps takaomontana), have been tested for their mating-type structure by Yokoyama et al (2003). Three contain the MAT1-1 idiomorph whereas 19 have the MAT1-2 idiomorph.…”
Section: C) Asexual Sordariomycetesmentioning
confidence: 99%
See 1 more Smart Citation